EVALUATING SUSTAINABILITY THROUGH RESOURCE EFFICIENCY: A CASE STUDY OF CIRCULAR ECONOMY PRACTICES IN THREE COMPANIES - Wael Brinsi (Oradea Journal of Business and Economics)
The concept of a circular economy (CE) aims to develop a closed-loop system that strives to minimize waste, which adversely impacts the environment. Besides the positive impact on the environment, the adoption of CE generates economic, social, and cultural benefits that encourage companies to shift from linear ‘take-produce-use-dump’ to circular models of product. In this paper, we explore the implementation of CBMs in three companies from different industries including key factors contributing to the successful implementation of CBMs, benefits and challenges. Through an examination of best practices of the case studies from different sectors (Fashion, Manufacturing, Electronics), these companies have significantly enhanced resource efficiency and sustainability, demonstrating the viability and benefits of circular practices.